Keamatan penggunaan, kemahiran swaawas dan orientasi privasi organisasi terhadap pengurusan privasi Facebook dalam kalangan penjawat awam di negeri Kedah: Satu analisis pengaruh - Junaidi, Abdul Rani @ Abdul Ghani (2016)
However, there have been many issues related to information privacy management which can contribute towards society perception on integrity among public servants. This study aimed to identify the effect of the intensity of the use of Facebook, selfmonitoring skills, and organization privacy orientation towards managing the Facebook privacy. The theoretical framework of this study is built upon the Theory of Communication Management. A cross-sectional survey was conducted among the civil servants from the state agencies, federal and statutory bodies of Kedah state. A total of 183 respondents, which were identified through a random sampling method, were involved for this study. The questionnaire survey consists of four instruments to measure variables, namely Facebook Intensity Scale, Scale Self-Monitoring, Organizational Privacy Orientation, and Facebook Privacy Management Scale. Data obtained, were analyzed descriptively in mean and standard deviation using SPSS. Inferential analysis was conducted using the Partial Least Square - Structural Equation Modeling (PLS- SEM) with the aid of SmartPLS 3.0. The results showed that organization privacy management and self-monitoring skills have a significant influence on the confidence level of 5% towards the intensity Facebook usage. In addition, the intensity of Facebook usage, organization privacy orientation and selfmonitoring skills also have significant influence on the management of Facebook privacy. This study describes the role of the individual evaluation factors and social environment of the organization in determining the Facebook privacy management. The findings of this study can be utilized to develop an awareness program which is related to the management of online information privacy to ensure the credibility of each public servant.